Penggunaan Metode Single Channel Untuk Mengoptimalkan Waktu Tunggu Pelanggan di Cafe Teras Coffe - Ariani, Lisa; Yuni, Elfi Zahra; Ritonga, Rista Andini; Anggraini, Dela; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
This research focuses on analyzing queues at the Teras Coffe cafe using the single channel method. Queues often occur at this cafe due to the high volume of visitors, which causes long waiting times for customers. The aim of this research is to optimize customer waiting time by understanding the existing queuing system. The method used in this research includes collecting primary data through interviews and direct observation in the field. The data obtained includes the time of customer arrival and the duration of service provided by the cashier. By using the single channel method, where there is only one service channel, this research aims to provide a clear picture of the expected waiting time and the number of customers waiting in the queue. The analysis results show that with better arrangements in the service system, waiting times can be minimized. It is hoped that this research can provide useful recommendations for cafe managers in improving service efficiency and customer satisfaction. Thus, this research not only provides insight into queue management, but also contributes to a better customer experience at the Teras Coffe cafe.